ANALISIS FAKTOR PENYEBAB KETERLAMBATAN PENGEMBALIAN BERKAS REKAM MEDIS RAWAT INAP RUMAH SAKIT PUSAT PERTAMINA - Anggia Lutfi Rohmawati; Feby Erawantini; Mochammad Choirur Roziqin (Politeknik Negeri Jember, 2021)
The process of medical record organizing through a series of activities including registration, processingmedical record data, auditing the contents of medical records, archiving, and presenting the information.One factor that supports the processing of medical record files is returning the medical record of patientswho have finished receiving health services from the inpatient unit. There were 323 (25%) files from 1276which were delayed when they returned. The purpose of this study was to analyze the factors which iscausing the delay in returning the inpatient medical record file at Pertamina Central Hospital with a behavioraltheory consisting of predisposing factors, enabling factors, and reinforcing factors. This type of research wasqualitative with data collection methods, namely interviews and observations. The subjects of this researchwere nurses, distributor officers and file monitoring officers inpatient. The results show that the lack of selfmotivation among officers both doctors and nurses as medical record filler and also distributor officers couldbe the cause of delay in returning the medical records of inpatients unit, the number of distributors who wereless and the distance of the inpatient room to the medical record room could cause a long delay in returningthe inpatient medical record file, the attitude and behavior of the inpatient file monitoring officer who doesnot request the medical record file that has not been returned for immediate return could cause a delay inreturn. The solution obtained from the problem is to increase self-motivation by increasing awareness of theresponsibilities from the doctor, distributor officers, and file monitoring officers when they are performing thetasks, as well as doing recalculation for distributor officers number.